ChemInform Abstract: Photoelectrochemical Water Splitting on Particulate ANbO2N (A: Ba, Sr) Photoanodes Prepared from Perovskite‐Type ANbO3. Issue 51 (5th December 2016) - Seo, Jeongsuk; Moriya, Yosuke; Kodera, Masanori; Hisatomi, Takashi; Minegishi, Tsutomu; Katayama, Masao; Domen, Kazunari
Abstract: Perovskite‐type ANbO2 N (A: Ba, Sr) is prepared by thermal nitriding of the title oxide precursors (Al2 O3 boats, 1173 K, 20 h, NH3 flow of 250 ml/min).